Pengembangan Multimedia Interaktif pada Pembelajaran Matematika Materi Persegi Panjang dan Segitiga di Sekolah Dasar - Dian Aprianty; Somakim Somakim; Ketang Wiyono (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
The use of interactive multimedia has a big influence in the world of education, especially mathematics learning. This development research aims to produce interactive multimedia product on learning rectangles and triangles for grade IV to facilitate and motivate students in understanding and mastering mathematical concepts. Media development uses the Alessi & Trollip development model which has three stages, namely planning, design, and development including alpha testing and product beta testing to determine its feasibility. Alpha test results, product that has been developed is declared valid after repairs are made to the product. The beta test results show that multimedia is declared practical after a product revision is made. The application of interactive multimedia that has been developed in learning has an impact on improving the learning outcomes of fourth-grade students of SDN 157 Palembang, namely 85.71 percent of students have reached the minimum completeness criteria with an N-gain average value of 0.65 with moderate criteria. Pemanfaatan multimedia interaktif memberikan pengaruh besar dalam dunia pendidikan khususnya pembelajaran matematika. Penelitian pengembangan ini bertujuan untuk menghasilkan produk multimedia interaktif pada pembelajaran persegi panjang dan segitiga untuk kelas IV guna mempermudah dan memotivasi peserta didik dalam memahami dan menguasai konsep matematika. Pengembangan media menggunakan model pengembangan Alessi & Trollip yang memiliki tiga tahapan yaitu perencanaan, desain dan pengembangan termasuk uji alpha dan uji beta produk untuk mengetahui kelayakannya. Hasil uji alpha, produk yang telah dikembangkan dinyatakan valid setelah dilakukan perbaikan terhadap produk. Hasil uji beta menunjukkan bahwa multimedia dinyatakan praktis setelah dilakukan revisi produk. Penerapan multimedia interaktif yang telah dikembangkan dalam pembelajaran berdampak terhadap peningkatan hasil belajar peserta didik kelas IV SDN 157 Palembang yaitu 85,71 persen peserta didik telah mencapai kriteria ketuntasan minimal dengan nilai rerata Ngain yaitu 0,65 dengan kriteria sedang.